2020
DOI: 10.1080/07294360.2019.1677569
|View full text |Cite
|
Sign up to set email alerts
|

Being more human: rooting learning analytics throughresistance andreconnection with the values of higher education

Abstract: Universities are now compelled to attend to metrics that (re)shape our conceptualisation of the student experience. New technologies such as learning analytics (LA) promise the ability to target personalised support to profiled 'at risk' students through mapping large-scale historic student engagement data such as attendance, library use, and virtual learning environment activity as well as demographic information and typical student outcomes. Yet serious ethical and implementation issues remain. Data-driven l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Dollinger and Lodge (2018) also emphasised this point in their paper about issues and barriers and the use of co-creation strategies to address them. Parkes et al (2020) also highlighted the importance of involving students from the outset (collecting and sharing data together) so that education becomes a democratic process. Our study adds to the work of those indicated here by further determining student understanding and concerns regarding LA so these views may be taken on board by institutions, thus allowing LA outcomes to meaningfully inform both policy and practice (for all stakeholders).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dollinger and Lodge (2018) also emphasised this point in their paper about issues and barriers and the use of co-creation strategies to address them. Parkes et al (2020) also highlighted the importance of involving students from the outset (collecting and sharing data together) so that education becomes a democratic process. Our study adds to the work of those indicated here by further determining student understanding and concerns regarding LA so these views may be taken on board by institutions, thus allowing LA outcomes to meaningfully inform both policy and practice (for all stakeholders).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sabuncuoglu and Halayqeh [24] investigated EFL learners' views on learner autonomy and the extent to which their views on their responsibilities, abilities, motivation, and their activities and behaviors in and out of the classroom are actually applied. Parkes et al [25] state that universities must resist the assumption that the "problem" of student retention rate and performance can be solved only by numbers and algorithms; rather, the work in Los Angeles must be based on a reconnection with agreed values related to the purposes of higher education, including democratic participation, recognition of diversity and personal experience, and the process of becoming.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive analytics have also been challenged about their reliance on standardised variables or indicators, with an emphasis that instructional contexts are critical to consider when using learning analytics, and that generic one-size-fits-all models of student success are overly crude and ineffective (Gasevic et al, 2016). Moreover, there have been impassioned calls to rediscover the humanity in learning and teaching through data, and reconnect teachers with students at a human level through an ethic of care (Parkes et al, 2020):…”
Section: Background Learning Analytics and Student Supportmentioning
confidence: 99%